Developing Global Leader: The Key to Enhance Japanese University Studentsʼ Participation in Overseas Programmes - Ming, Lau Chung (Archives of Business Research, 2024)
Prompted by a shortage of global talent, Japan is making efforts to nurture the necessary human resources. The role of any university education cannot be ignored; however, various hurdles associated with several training programmes must be overcome, in particular the implementation of overseas programmes. If any overseas programmes are able to execute successfully, they can provide significant contributions to developing global minds of university students. This study empirically examines the degree of Japanese university students’ participation in overseas training programmes with teaching staff as companions. A total of 91 students from a national university in Japan were asked to complete a questionnaire and an independent sample t-test was used for data analysis. This study’s findings suggest that female students and students who had experience abroad prefer to have a teaching staff companion during their participation in overseas programmes. Japanese universities should consider increasing their support by using teaching staff to enhance the development of global talent through overseas education programmes.